2020
DOI: 10.1038/s41467-019-14238-3
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of pyrazinamide activity on Mycobacterium tuberculosis PanD

Abstract: Pyrazinamide has been a mainstay in the multidrug regimens used to treat tuberculosis. It is active against the persistent, non-replicating mycobacteria responsible for the protracted therapy required to cure tuberculosis. Pyrazinamide is a pro-drug that is converted into pyrazinoic acid (POA) by pyrazinamidase, however, the exact target of the drug has been difficult to determine. Here we show the enzyme PanD binds POA in its active site in a manner consistent with competitive inhibition. The active site is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 28 publications
2
67
0
2
Order By: Relevance
“…PZA is a prodrug that in acidic conditions is hydrolyzed by pyrazinamidase to pyrazinoic acid (POA); indeed, most of the PZA clinical resistance arises from the loss of function mutations in pncA [ 120 ]. Multiple mechanisms of action and targets have been reported for PZA [ 120 ] including the dissipation of PMF, even if recent studies have established that PanD is the primary target of PZA [ 121 ].…”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
“…PZA is a prodrug that in acidic conditions is hydrolyzed by pyrazinamidase to pyrazinoic acid (POA); indeed, most of the PZA clinical resistance arises from the loss of function mutations in pncA [ 120 ]. Multiple mechanisms of action and targets have been reported for PZA [ 120 ] including the dissipation of PMF, even if recent studies have established that PanD is the primary target of PZA [ 121 ].…”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
“…Protonated POA is able to accumulate and further disrupt membrane potential, membrane transport and intrabacterial pH31 . Recent structural and biochemical studies, clearly demonstrated that POA molecules are also able to covalently bind the Mtb protein PanD in vitro35,58 .Although the bacterial localisation of PanD is unknown, it is possible that CoA biosynthesis enzyme might localise at the inner leaflet of the bacterial cytoplasmic membrane to meet the requirement of specific lipid biosynthesis pathways as it was previously shown between the FAS-II and the mycolic acid synthesis machineries59 .Thus, host cell environments and Mtb intracellular localisation affect antibiotic efficacy, arguing that different antibiotics are needed to target heterogeneous intracellular bacterial populations. These results provide an explanation for the observed sterilising activity of PZA in the clinic but also contributes to a conceptual framework for a host cell dependent combined drug therapy in the context of TB.…”
mentioning
confidence: 99%
“…The exact active species (parent compounds vs. hydrolysed POA) and its MoA on the molecular level are to be elucidated. However, based on the recent biochemical and crystallographic investigations of PanD [12], the most prominent target of PZA, we conclude that our compounds do not act in their non-hydrolysed form against this target, as the binding cavity at the active site of PanD is too small to accommodate anything bigger than POA or 6-Cl-POA.…”
Section: Discussionmentioning
confidence: 82%
“…However, nowadays several specific enzymatic targets are being studied. Notable is the inhibition of fatty acid synthase I (FAS-I) [9,10], the disruption of trans-translation via interaction with ribosomal protein S1 (RpsA) [11], the inhibition of aspartate decarboxylase (PanD) [12], and the inhibition of quinolinic acid phosphoribosyltransferase (QAPRTase) [13]. Several other proteins have been suggested as targets of PZA/POA [14][15][16][17]; however, PanD has recently been suggested by some authors as the likely prevalent target [18].…”
Section: Introductionmentioning
confidence: 99%